Pre-service teachers’ emotional experience: Characteristics, dynamics and sources amid the teaching practicum - Ji, Yilong; Oubibi, Mohamed; Chen, Siyuan; Yin, Yuxin; Zhou, Yueliang (Frontiers in Psychology, 2022)
The teaching practice of pre-service teachers is emotional labor, which involves a series of emotional experiences. This study is based on a qualitative analysis of online emotional diaries related to emotional experience expression by 120 Chinese pre-service teachers before, during, and after teaching practice. The results found that: from the perspective of emotional experience characteristics, the pre-service teachers experienced complex, diverse and scattered emotional experiences, with as many as 30 types, 15 of which were positive emotions (e.g., Caring, Happy, Excited), and 15 were negative emotions (e.g., Nervous, Tired, Confused). The numbers of positive emotions are more than negative emotions. From the perspective of emotional experience dynamics, the emotional trajectories of pre-service teachers are complex and constantly evolving, and positive emotions and negative emotions are mutually converted. With the deepening of teaching practice, the positive emotions of pre-service teachers gradually decrease, and the negative emotions increase significantly. From the perspective of emotional experience sources, organizational factors affect the emotional experience, personal factors, and background factors.